Pengembangan Aplikasi Strategi Pencegahan Perilaku Perundungan (Bullying) pada Sekolah Dasar di Kota Jambi - Neni Heryani; Asmuni Asmuni; Atika F.D Nasution (Universitas Baiturrahim, 2020)
AbstractBullying behavior can result in the growth and development of a child, namely trauma and fear so that children do not want to go to school and experience disruption in the learning process. During the period of 2002-2005 there were 30 suicides which happened to victims of abuse at the age range of 6-15 years. Another impact of abuse behavior in childhood is closely related to anti-social behavior in the future after the child grows into adolescents and adults. This type of research and development. This research was conducted in an elementary school environment in the city of Jambi. The population was 48,043 students and 138 research samples. The results of this study the perpetrators of bullying are mostly done by classmates by 77%. The target of classmates bullying was 73%, the location of the harassment was mostly done in the classroom by 69.6%. The incidence of bullying is low around 45.7% and the incidence of bullying is high at 54.3%. The conclusion is the incidence of bullying with the grade level of elementary school students does not have a significant relationship. The incidence of bullying with gender does not have a significant relationship. The incidence of bullying with the perpetrator or victim has a significant relationship. There is a significant difference in knowledge in the use of modules and applications with a p-value of 0,000. the use of applications is more effective than the use of modules with a p-value of 0,000